Effects of kinsenoside, a potential immunosuppressive drug for autoimmune hepatitis, on dendritic cells/CD8+T cells communication in mice. Issue 6 (28th October 2016) - Xiang, Ming; Liu, Tingting; Tan, Wanyue; Ren, Hongyu; Li, Hua; Liu, Junjun; Cao, Hui; Cheng, Qi; Liu, Xiulan; Zhu, Hucheng; Tuo, Yali; Wang, Jianping; et al.
Abstract : The central purpose of this study was to investigate therapeutic effects of the botanical derivative, kinsenoside (KD), in experimental autoimmune hepatitis (AIH). Treatment with KD substantially reduced hepatic histopathological damage, induced by lymphocyte infiltration and proinflammatory cytokines, in concanavalin A‐induced T‐cell‐mediated hepatitis, and in dendritic cells (DCs) loaded with hepatocellular carcinoma cells (DC/Hepa1‐6) induced murine AIH. Interactions between immune cells after KD treatment in AIH were detected by anti‐CD8 antibody blocking, CD8 + T cell sorting, and vaccinated mice with KD‐pretreated DCs in a DC/Hepa1‐6 model. These results showed that KD inhibited the elevated expressions of CD86 and major histocompatibility complex II, densities of chemokine receptor C‐C chemokine receptor type 7, and extensive migration to lymph nodes, and increased the programmed death ligand 1 level of DCs, followed by suppressing CD8 + T cells, characterized as low differentiation and cytotoxicity, and eliciting cytokines balance. Furthermore, biochemical analysis, two‐dimensional fingerprint screen and three‐dimensional molecular docking results showed that KD bound to the vascular endothelial growth factor receptor 2 (VEGFR2) kinase domain, which inhibited the metabolism‐related phosphatidylinositol 3 kinase/protein kinase B (PI3K‐AKT) pathway in DCs and DC‐modulated CD8 + T cells to lower the mitochondrial membrane potential and glucose/lipid utilization ratio in both cells. KD reversed activation of the PI3K‐AKT pathway by 740 Y‐P (PI3K agonist), thereby impeding the translocation and dimerization of signal transducer and activators of transcription (STAT) 3 and synergistically blocking the inflammation‐related Janus kinase (JAK) 2/STAT3 pathway in DCs and DC‐modulated T cells. Conclusion : KD treatment elicits immunosuppression against autoimmune liver injury by targeting VEGFR2, followed by diminishing the cross‐talk of metabolism‐related PI3K‐AKT and inflammation‐related JAK2‐STAT3 pathways, and thereby disrupts DC‐induced cross‐priming of CD8 + T cell responses. (Hepatology 2016;64:2135‐2150).